Asphalt pavement rutting simulated using granular micromechanics-based rate-dependent damage-plasticity model. Issue Volume 20:Issued 9(2019) (2nd September 2019) - Misra, Anil; Singh, Viraj; Darabi, Masoud K.
Abstract: Repeated application of vehicle loads on the asphalt pavement creates permanent deformations and surface cracks. Simulation of this pavement distress has posed severe challenges due to the granular nature of the pavement materials. In this paper, the granular micromechanics approach is used in a thermo-mechanical framework to obtain the constitutive relationships for the non-linear rate-dependent granular materials with damage and plasticity. The developed constitutive relationships were validated and verified with experimental data and implemented into a non-standard finite-element (FE) framework to simulate asphalt pavement performance under the repeated traffic load. The FE model was subjected to different repeated load levels to demonstrate response nonlinearity. The applied load was subsequently removed and pavement was allowed to recover to a stress free condition to obtain the permanent deformation. The simulations results demonstrated that 30% increase in the applied load causes approximately 127% increase in the rutting depth at the centre of the applied load. Critically horizontal tensile plastic strains were observed near tire edge, indicating top-down cracking of pavement under the applied load. The presented approach provides an alternative for simulating asphalt pavement rutting by incorporating the effects of micro-scale mechanisms on the macro-scale rutting response in an FE framework. The advantage of the granular micromechanical approach is that, the damage, plastic potential and flow rule are defined using simple 1d functions at micro-scale, in contrast to tensorial formulation of complex plastic potentials, damage functions and rules for their evolution in conventional approaches.